2018
DOI: 10.30954/0424-2513.4.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

Managing Genetic Resources in Temperate Fruit Crops

Abstract: Biodiversity representing variation within genetic resources at gene, population, species and ecosystem level is our heritage that makes a key contribution to well-being and sustainable development. India is one of the mega biodiversity-rich countries of the world, with only 2.4% of the land area; it accounts for 7.8% of all the recorded species on this planet and ranks 10 th in the world and 4 th in Asia in plant diversity. This richness of species and genetic diversity provides many opportunities, which can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
(6 reference statements)
1
1
1
Order By: Relevance
“…In agreement with our results, Esmat et al [22] showed that the platelet/spleen diameter at a cut-off point of 1326.6 can predict OV with 96.3% sensitivity, 83.3% specificity, 96.3% PPV, and 83.3% NPV. In comparison to the current results, Qamar et al [23] and Hassan,et al [24] found that platelets/splenic longitudinal diameter (PLT/SLD) ratio did not revealed a significant difference in patients with and without OV, suggesting that these method cannot be used in the prediction of the presence of varices. This conflict may be attributed to differences in the severity of liver disease in our patients as 60 % of group II cases in our study were Child B &C and 90% of group I were Child A, despite the previous studies included patients with Child "A" and early "B" liver cirrhosis who had less impairment of platelet.…”
Section: Discussioncontrasting
confidence: 89%
“…In agreement with our results, Esmat et al [22] showed that the platelet/spleen diameter at a cut-off point of 1326.6 can predict OV with 96.3% sensitivity, 83.3% specificity, 96.3% PPV, and 83.3% NPV. In comparison to the current results, Qamar et al [23] and Hassan,et al [24] found that platelets/splenic longitudinal diameter (PLT/SLD) ratio did not revealed a significant difference in patients with and without OV, suggesting that these method cannot be used in the prediction of the presence of varices. This conflict may be attributed to differences in the severity of liver disease in our patients as 60 % of group II cases in our study were Child B &C and 90% of group I were Child A, despite the previous studies included patients with Child "A" and early "B" liver cirrhosis who had less impairment of platelet.…”
Section: Discussioncontrasting
confidence: 89%
“…In the current study and according to the multivariate logistic regression analysis for predictors of OV, BAL was the only predictor of OV presence. This result was in agreement with Hassan,et al [19], who reported that BAL, PVD, SVD and SLD were good non-invasive predictors for the presence of OV in cirrhotics with the superiority of ammonia and PVD, and was in disagreement with Ramzy et al [16].…”
Section: Discussionsupporting
confidence: 88%
“…Recent progress in cryopreservation technology has demonstrated the safe, efficient, and economical advantages of long-term preservation. Therefore, the technology has undergone significant development during the last two decades, enabling the cryobanking of many crops such as apple, apricot, banana, blueberry, and garlic [ 8 , 9 , 10 , 11 ]. The cryopreservation protocols for strawberry have been developed using different methods [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%